Fatigue crack growth rate in mode I of a carbon fiber 5HS weave composite laminate processed via RTM - Shiino, Marcos Yutaka [UNESP] (2014)
Delamination or crack propagation between plies is a critical issue for structural composites. In viewing this issue and the large application of woven fabrics in structural applications, especially the ones that requires high drapeability to be preformed in a RTM mold cavity such as the asymmetric ones, e.g HS series, this research aimed in dynamically testing the carbon fiber 5HS/RTM6 epoxy composites under opening mode using DCB set up in order to investigate the crack growth rate behavior in an irregular surface produced by the fabric waviness. The evaluation of the energy involved in each crack increment was based on the Irwin-Kies equation using compliance beam theory. The tests were conducted at constant stress ratio of R=0.1 with displacement control, frequency of 10 Hz, in accordance to ASTM E647-00 for measurement of crack growth rate. The results showed large scatter when compared to unidirectional carbon fiber composites due to damage accumulation at the fill tows.